Risk of osteonecrosis in systemic lupus erythematosus: An 11-year Chinese single-center cohort study - Long, Yin; Zhang, Shangzhu; Zhao, Jiuliang; You, Hanxiao; Zhang, Li; Li, Jing; Leng, Xiaomei; Wang, Qian; Tian, Xinping; Li, Mengtao; Zeng, Xiaofeng (Lupus, 2021)
Objective Osteonecrosis (ON), which can lead to physical disability, is a common complication of systemic lupus erythematosus (SLE). The purpose of this study was to determine the prevalence of ON and identify possible risk factors in Chinese SLE patients. Methods SLE patients who fulfilled the 1997 American College of Rheumatology SLE classification criteria were recruited from the Peking Union Medical College Hospital. The chi-square test (χ 2 test) and multivariate regression analyses were used to evaluate risk factors. The Cox proportional-hazards model was used to construct the survival curves and estimate the simultaneous effects of prognostic factors on survival. Results We consecutively enrolled 1,158 patients, of which 88 patients (7.6%) developed ON. Among ON patients, 57.1% of patients had isolated femoral head necrosis and 42.9% had multiple joint involvement. The mean age of ON patients (24.62 ± 8.89 years) was significantly younger than SLE patients without ON (27.23 ± 10.16 years, p = 0.09). The ON group presented with a much longer disease course (10.68 ± 5.97 years, p < 0.001) and increased incidence of arthritis, kidney, and central nervous system (CNS) involvement (65.9% [p < 0.05], 57.6% [p < 0.05], and 16.5% [p < 0.05], respectively, in the ON group). ON patients were more likely to be treated with glucocorticoid (GC) and to receive a high dose of prednisolone at the initial stage of SLE (p < 0.05). The percentage of patients who received hydroxychloroquine was much higher in the control group (p < 0.001). Cox regression analysis suggested that CNS involvement and GC therapy were two independent risk factors for ON in SLE patients. The presence of anti-phospholipid antibodies (aPLs) was a risk factor for multiple joint necrosis (odds ratio: 6.28, p = 0.009). Conclusions ON remains a serious and irreversible complication in SLE. In addition to glucocorticoid therapy, we found that CNS system involvement was a risk factor for ON, while the administration of hydroxychloroquine was a protective factor. The clinical characteristics of multiple site ON patients were distinct from isolated femoral head necrosis patients. The presence of aPLs was a risk factor for multiple site osteonecrosis.